2010
DOI: 10.1016/j.bbamem.2010.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Sphingomyelin analogs with branched N-acyl chains: The position of branching dramatically affects acyl chain order and sterol interactions in bilayer membranes

Abstract: Sphingolipids have been found to have single methyl branchings both in their long-chain base and in their N-linked acyl chains. In this study we determined how methyl-branching in the N-linked acyl chain of sphingomyelin (SM) affected their membrane properties. SM analogs with a single methyl-branching at carbon 15 (of a 17:0 acyl chain; anteiso) had a lower gel-liquid transition temperature as compared to an iso-branched SM analog. Phytanoyl SM (methyls at carbons 3, 7, 11 and 15) as well as a SM analog with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 56 publications
1
42
1
Order By: Relevance
“…Cholesterol is known to affect membrane fluidity via its effects on phospholipid acyl chain order [20]. With our bilayer model (POPC: PSM 4:1) cholesterol will increase mostly PSM acyl chain order (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cholesterol is known to affect membrane fluidity via its effects on phospholipid acyl chain order [20]. With our bilayer model (POPC: PSM 4:1) cholesterol will increase mostly PSM acyl chain order (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Palmitoyl SM (PSM) was purified from egg SM using preparative HPLC on a reverse phase (C18) column, as described previously [20]. Cholesterol, calcein and Sephacryl S200HR were obtained from Sigma/Aldrich (St. Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…D- erythro-N -palmitoyl sphingomyelin (PSM) was isolated from egg sphingomyelin as described (38). Cholesterol and Triton X-100 were from Sigma/Aldrich (St. Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Since pure stearoyl SM membrane forms gel phase below the phase transition temperature (44 C) (29), which provides broadened solid-state NMR spectra, it is necessary to measure the spectra above 44 C. In addition, in our previous report (17), we found that there is no critical difference in the 2 H NMR spectra of deuterated SM bilayers between 45 C and 50 C in either the presence or absence of Chol; thus, the NMR spectra were recorded at 45 C for SM and SM-Chol membranes. In membrane environments, lipid molecules undergo fast axial rotation, giving rise to an axially symmetric signal pattern that is defined by the two tensor values d ┴ and d // .…”
Section: And 15 N Csa Of Sm Amidesmentioning
confidence: 99%